Drug Addiction - A Threat To Societal Development: Society’s Unity In The Fight Against It (Eurasian Scientific Herald, 2025)
The article analyzes issues related to combating narcotic drugs, which are among the most pressing global problems in today’s world. It also examines the causes and consequences of drug addiction and presents scientific proposals and recommendations on measures to prevent and combat it.